Analisis Resepsi Fungsional dalam Tradisi Pembacaan 124.000 Surah al-Ikhlas di Desa Pangkatrejo Lamongan - Ahmad Fikri (Javano Islamicus, 2026)
This study examines the practice of Living Qur'an in the form of reading 124,000 times surah al-Ikhlāṣ in a series of deaths in Pangkatrejo Village, Lamongan. This phenomenon is important to study because it is often carried out as a ceremonial routine withoutadequate understanding of its meaning and function. The research describes the history, foundations, and implementation of the tradition, then analyzes it using Ahmad Rafiq's functional reception theory with in the framework of the Living Qur'an. The methodused is qualitative-descriptive field research through observation, interviews, and documentation. The findings show that this tradition represents a functional reception that is performative in nature: the textis practiced as an effort to pray for the deceased as well as to bind social solidarity. Its preservation occurs through three channels of transmission literary references, networks of kiai-santri, and discursive reproduction and has undergone transformations in the number of participants, locations, and counting media.